2006
DOI: 10.1007/s10461-006-9117-3
|View full text |Cite
|
Sign up to set email alerts
|

Conflicting Messages: How Criminal HIV Disclosure Laws Undermine Public Health Efforts to Control the Spread of HIV

Abstract: Twenty-three U.S. states currently have laws that make it a crime for persons who have HIV to engage in various sexual behaviors without, in most cases, disclosing their HIV-positive status to prospective sex partners. As structural interventions aimed at reducing new HIV infections, the laws ideally should complement the HIV prevention efforts of public health professionals. Unfortunately, they do not. This article demonstrates how HIV disclosure laws disregard or discount the effectiveness of universal preca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(86 citation statements)
references
References 45 publications
1
78
0
4
Order By: Relevance
“…Compounding the fact that serostatus non-disclosure criminal law likely has a small HIV prevention effect is that other authors suggest that these legal precedents might consequently decrease HIV testing among PHAs who are unaware of their serostatus (Cameron 2009;Symington 2009;UNAIDS 2002;Galletly and Pinkerton 2006;Bennett et al 2000;Lazzarini et al 2002;Wolf and Vezina 2004). Because this group of PHAs is disproportionately implicated in continued HIV transmission, and because the impact fraction model suggests that the proportional significance of this group makes it is a priority population for HIV prevention, a reduction in HIV testing, serostatus awareness and the HIV prevention outcomes that often correspond with serostatus awareness (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Compounding the fact that serostatus non-disclosure criminal law likely has a small HIV prevention effect is that other authors suggest that these legal precedents might consequently decrease HIV testing among PHAs who are unaware of their serostatus (Cameron 2009;Symington 2009;UNAIDS 2002;Galletly and Pinkerton 2006;Bennett et al 2000;Lazzarini et al 2002;Wolf and Vezina 2004). Because this group of PHAs is disproportionately implicated in continued HIV transmission, and because the impact fraction model suggests that the proportional significance of this group makes it is a priority population for HIV prevention, a reduction in HIV testing, serostatus awareness and the HIV prevention outcomes that often correspond with serostatus awareness (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…As a scientific outlet, AIDS and Behavior shares this responsibility. Articles published in the journal have been important in past policy initiatives [29][30][31][32][33]. Continued progress in controlling HIV requires us to become scientist-activists and hold ourselves accountable for demanding evidence-based public health policies.…”
Section: Willfully Allowing Hiv To Spread Among Citizens Is a Crime Amentioning
confidence: 99%
“…Therefore, the implication of this study showed that HIV mandatory disclosure law might not promote the societal context of encouraging safer sex and regular HIV testing and instead reinforced the societal stigma and rejection of the individuals with HIV. This was further explained by Galletly et al, who argued that there was no significant evidence that disclosure was effective as a preventive strategy to reduce HIV transmission through condom use [68]. Instead, the disclosure law undermined efforts to reinforce the use of condom as a societal and behavioural norm and instead promoted HIV stigma and fear.…”
Section: Effectiveness Of the Lawmentioning
confidence: 99%